2011
DOI: 10.1242/dev.057323
|View full text |Cite
|
Sign up to set email alerts
|

FGF/MAPK/Ets signaling renders pigment cell precursors competent to respond to Wnt signal by directly controllingCi-Tcftranscription

Abstract: SUMMARYFGF and Wnt pathways constitute two fundamental signaling cascades, which appear to crosstalk in cooperative or antagonistic fashions in several developmental processes. In vertebrates, both cascades are involved in pigment cell development, but the possible interplay between FGF and Wnt remains to be elucidated. In this study, we have investigated the role of FGF and Wnt signaling in development of the pigment cells in the sensory organs of C. intestinalis. This species possesses the basic features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 75 publications
4
89
0
Order By: Relevance
“…While the gene encoding Vent has been lost from the ascidian genome, Msx in ascidians is also expressed in nonneural ectoderm but extends into the lateral neural plate like in vertebrates, where it overlaps with Pax3/7, Snail, Ets, and elevated Zic expression (Corbo, Erives, DiGregorio, Chang, & Levine, 1997;Gostling & Shimeld, 2003;Imai et al, 2004;Ma et al, 1996;Mazet, Hutt, Millard, & Shimeld, 2003;Mazet, Yu, Liberles, Holland, & Shimeld, 2003;Squarzoni, Parveen, Zanetti, Ristoratore, & Spagnuolo, 2011;Wada, Holland, & Satoh, 1996;Wada & Saiga, 2002;. These TFs may help to define a lateral neural plate identity as in vertebrates.…”
Section: Ectodermal Patterningmentioning
confidence: 99%
“…While the gene encoding Vent has been lost from the ascidian genome, Msx in ascidians is also expressed in nonneural ectoderm but extends into the lateral neural plate like in vertebrates, where it overlaps with Pax3/7, Snail, Ets, and elevated Zic expression (Corbo, Erives, DiGregorio, Chang, & Levine, 1997;Gostling & Shimeld, 2003;Imai et al, 2004;Ma et al, 1996;Mazet, Hutt, Millard, & Shimeld, 2003;Mazet, Yu, Liberles, Holland, & Shimeld, 2003;Squarzoni, Parveen, Zanetti, Ristoratore, & Spagnuolo, 2011;Wada, Holland, & Satoh, 1996;Wada & Saiga, 2002;. These TFs may help to define a lateral neural plate identity as in vertebrates.…”
Section: Ectodermal Patterningmentioning
confidence: 99%
“…We recently showed that the FGF/MAPK/Ets pathway is responsible for pigmented cell precursor specification, starting from the late gastrula stage, by rendering their progenies competent to respond to a Wnt signal17. However, the FGF signalling downstream targets involved in the regulatory architecture of pigment cell lineage formation remain uncharacterized.…”
mentioning
confidence: 99%
“…In solitary ascidian species, STP expression and functions during ontogenic stages have been elucidated for Wnt/b-catenin (Niwano et al, 2009;Hudson et al, 2013), TGF-b (Kobayashi et al, 1999;Kobayashi and Makabe, 2001;Hino et al, 2003;Kawashima et al, 2005;Christiaen et al, 2010;Nishide et al, 2012) and MAPK/ ERK (Bertrand et al, 2003;Hudson et al, 2003;Nishida, 2003;Pasini et al, 2006;Chambon et al, 2007;Sakabe et al, 2006) pathways alone, or in combination with other STPs (Hudson et al, 2007;Lemaire, 2009;Pasini et al, 2012;Sasakura et al, 2012;Squarzoni et al, 2011). This has not been extensively studied in colonial species where astogenic and ontogenic pathways are developing side by side and in concert.…”
Section: Discussionmentioning
confidence: 99%